Cardiac perfusion by positron emission tomography - Nammas Wail; Maaniitty Teemu; Knuuti Juhani; Saraste Antti (WILEY, 2022)
Myocardial perfusion imaging (MPI) with positron emission tomography (PET) is an established tool for evaluation of obstructive coronary artery disease (CAD). The contemporary 3-dimensional scanner technology and the state-of-the-art MPI radionuclide tracers and pharmacological stress agents, as well as the cutting-edge image reconstruction techniques and data analysis software, have all enabled accurate, reliable and reproducible quantification of absolute myocardial blood flow (MBF), and henceforth calculation of myocardial flow reserve (MFR) in several clinical scenarios. In patients with suspected coronary artery disease, both absolute stress MBF and MFR can identify myocardial territories subtended by epicardial coronary arteries with haemodynamically significant stenosis, as defined by invasive coronary fractional flow reserve measurement. In particular, absolute stress MBF and MFR offered incremental prognostic information for predicting adverse cardiac outcome, and hence for better patient risk stratification, over those provided by traditional clinical risk predictors. This article reviews the available evidence to support the translation of the current techniques and technologies into a useful decision-making tool in real-world clinical practice.